Soluble Axl is an accurate biomarker of cirrhosis and hepatocellular carcinoma development: results from a large scale multicenter analysis - Dengler, Mirko; Klöters-Plachky, Petra; Weiss, Karl Heinz; Gotthardt, Daniel (OncoTarget, 2017)
Oncotarget | https://doi.org/10.18632/oncotarget.17598 Mirko Dengler, Katharina Staufer, Heidemarie Huber, Rudolf Stauber, Heike Bantel, Karl Heinz Weiss, Patrick Starlinger, Hannelore Pock, Petra Klöters-...